My Health Safety Environment Using Web Responsive (MyHSE) - Deveshwaran, Arumugam (2023)
The development of My Health Safety Environment (MyHSE), a web-based responsive system created to address important issues in the occupational safety and health (OSH) sector, is described in this thesis. The proposed system provides a centralised platform for accessing OSH services in an effort to address issues like scams, drawn-out verification procedures, and a lack of dependable service providers. MyHSE's main goal is to offer a dependable and user-friendly platform so that OSH service providers can showcase their offerings and subscribers can quickly access and reserve these services. The system aims to guarantee the legitimacy of service providers by integrating a competent person verification mechanism that makes use of certificates and registration numbers. The Rapid Application Development (RAD) methodology, which emphasises iterative prototyping and user involvement, was used in the development of MyHSE. The RAD approach made it easier to quickly create prototypes and iteratively improve them in response to user feedback. The methodology allowed for regular revisions and adaptations, guaranteeing that the system's functionality and design precisely met the changing needs of both service providers and subscribers. MyHSE offers a number of crucial features that will improve the customer experience in the OSH sector. Providers of OSH services can quickly upload and advertise the services they provide, complete with pertinent contact information and service specifics. Subscribers, in turn, have access to a wide range of trustworthy services, making booking and service requests easier. MyHSE uses a strong competent person verification mechanism to foster trust and dependability. Service providers must go through verification, during which the validity of their licences and registration numbers is examined. Subscribers are reassured by this rigorous verification process that they are working with qualified and competent professionals.